2012
DOI: 10.1084/jem.20112145
|View full text |Cite
|
Sign up to set email alerts
|

A role for the RNA pol II–associated PAF complex in AID-induced immune diversification

Abstract: Antibody diversification requires the DNA deaminase AID to induce DNA instability at immunoglobulin (Ig) loci upon B cell stimulation. For efficient cytosine deamination, AID requires single-stranded DNA and needs to gain access to Ig loci, with RNA pol II transcription possibly providing both aspects. To understand these mechanisms, we isolated and characterized endogenous AID-containing protein complexes from the chromatin of diversifying B cells. The majority of proteins associated with AID belonged to RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…AID's specificity for transcription-associated ssDNA appears to be facilitated by interactions with multiple proteins present in the transcription apparatus (Chaudhuri et al, 2004, Pavri et al, 2010, Willmann et al, 2012) as well as long non-coding RNAs transcribed from the immunoglobulin switch regions (Zheng et al, 2015). In the absence of direct recruitment to a specific ssDNA substrate, the activity of the majority of APOBECs may be dictated by the abundance and persistence of the ssDNA intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…AID's specificity for transcription-associated ssDNA appears to be facilitated by interactions with multiple proteins present in the transcription apparatus (Chaudhuri et al, 2004, Pavri et al, 2010, Willmann et al, 2012) as well as long non-coding RNAs transcribed from the immunoglobulin switch regions (Zheng et al, 2015). In the absence of direct recruitment to a specific ssDNA substrate, the activity of the majority of APOBECs may be dictated by the abundance and persistence of the ssDNA intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…However, pausing of RNAPII during transcription can lead to more extensive exposure of ssDNA in the transcription bubble (Gómez‐González & Aguilera, 2007) and a number of studies have suggested that transcriptional pausing is also a key mechanism to attract AID to the IgV mutation domain (Kenter, 2012). Supporting this idea, AID has been physically linked to RNAPII through its ability to binding the RNAPII‐associated processivity factor Spt5 (Pavri et al , 2010), the PAF complex (Willmann et al , 2012) and components of the exosome (Basu et al , 2011), the latter observation providing a potentially elegant solution to the problem of AID targeting both strands of DNA, as the exosome could facilitate exposure of the template strand in addition to the coding strand.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that associate with AID and might facilitate its recruitment to super-enhancers are the RNA Pol II complex 53 , the Pol II-associated factors SPT5 50 and SPT6 54 , the Pol II elongation PAF complex 55 , and chromatin modifiers, such as KAP1 56 . As discussed in detail in the next two subsections, the RNA exosome complex 57 and the splicing machinery might also play a role 58, 59 .…”
Section: What Recruits Aid Activity To Off-target Sites?mentioning
confidence: 99%